Studies on Salmonella from Floor Litter of 60 Broiler Chicken Houses in Nova Scotia - Long, J. R. (1980)
Fifteen floor litter samples were collected from each of 60 broiler chicken houses in Nova Scotia. Salmonella was recovered from 270 litter samples (30%) in 33 of 60 (55%) houses. All isolates were serotyped. Salmonella heidelberg and S. infantis were the most common of the 13 serotypes found. Isolates of selected serotypes were phage typed. Most isolates were susceptible to all common antimicrobial agents.